In Vitro Multiplication Of Gymnema Sylvestre R. Br. Through Nodal Explants - R. MANONMANI; P. FRANCISCA (International Journal of Pharma and Bio Sciences, 2012)
Gymnema sylvestre R. Br. a very useful medicinal plant belongs to the family Asclepiadaceae. Nodal explants of Gymnema sylvestre were used for in vitro multiplication on a medium containing various concentrations of growth regulators such as BA and NAA. Among the combinations used, MS medium fortified with BA at 1.0 mg/l was found to be suitable for induction of multiple shoots. The shoots were observed within 1 week of inoculation. The regenerated shoots were transferred to rooting media supplemented with different concentrations of NAA. The highest percentage of rooting was observed with NAA at 1.0 mg/l. The regenerated plantlets were transferred to the field after acclimatization.